Design a new proposed route optimization scheme based NEMO-Centric MANEMO (NCM) - Mousa, Ahmed A.; Hassan Abdalla Hashim, Aisha; Khateeb, Khalid Al; Khalifa, Othman Omran; Adibah, Huda Adibah (Institute of Electrical and Electronics Engineers Inc, 2014)
Route Optimization (RO) refers to any approach that optimizes the transmission of packets between a Mobile Network Node/Mobile Router and a Corresponding Node/Home Agent. RO would mean that a binding between the address of an MNN/MR and the location of the mobile network is registered at the CE/HA. Technically, route optimization mechanism comes up with a complementing solution for the pinball problem by avoiding the MRHA Bidirectional Tunnel(BT) that is to be used. This paper discusses the RO issues for NEMO and more specifically issues of Nested NEMO such astunneling redundant, HA dependency, processing delay, bottleneck, traffic congestion, ER selection, and scalability in the design consideration. In order to address NEMO ROsuboptimal, this work utilizes the NCM protocol plus to PHA. The proposed MANEMO RO scheme is a layer three solution to support RO for mobile networks. Additionally, the paper proposes the design to address Nested NEMO issues in a post disaster scenario by using Proxy Home Agent (PHA) in the infrastructure with using Neighbor Discovery protocol(TDP/NINA) for localizing communications. Thus, thesignaling message flow and the algorithm are written to give proposed scheme more flexibility